Faults Get Colder Through Transient Granular Vortices. Issue 6 (25th March 2018) - Einav, I.; Rognon, P.; Miller, T.; Sulem, J.
Abstract: Fault temperatures govern their weakening and control the dynamics of earthquakes during slip. Despite predictions of significant temperature rise within fault gouges during earthquake events, observations of frictional melting zones along exhumed faults are relatively rare. Could there be a heat transfer mechanism, previously not considered, that results in ubiquitously colder faults during earthquakes? We demonstrate that the remarkable, previously neglected mechanism of heat transfer through transient granular vortices may be at the core of this. We present and analyze results from perpetual simple shear experiments on a system of granular disks with which we are able to quantify the sizes and lifetimes of granular vortices within fault gouges during earthquakes. We then develop a formula that captures the contribution these vortices have on heat transfer. Using this formula, we show that crustal faults such as those in the San Andreas system may experience a maximum temperature rise 5 to 10 times lower than previously thought. Plain Language Summary: The instability of earthquakes has long been attributed to fault weakening mechanisms, including thermal pressurization, melting, silica gel lubrication, and mineral decomposition. Research in this area has continuously fascinated the broad community, including many publications in the world's leading scientific journals. Predicting temperature rise is at the core of those studies, since temperature controls the activation of all of those weakening factors. However, past predictions of temperature rise have systematically overlooked the potential effects of transient granular vortices, which are ubiquitous in sheared fault gouges. Our current paper evaluates their contribution to heat transfer, which is found to be enormous indeed. Specifically, for the case of mature faults in the San Andreas system, we show that transient granular vortices produce an effective thermal diffusivity 1, 000 times higher than the one previously considered through conduction only. This is an important finding, which dramatically affects the heat budget and temperature of sheared fault gouges during earthquakes. Key Points: Perpetual simple shear experiments are carried out with which transient granular vortices are analyzed Transient granular vortices dramatically enhance the effective thermal diffusivity in sheared fault gouges The heat equation of fault gouges during earthquakes is generalized in light of convection by granular vortices